THE EFFECT OF ITERATIONS, COLLABORATION, AND DESIGNING GEOGEBRA MODULES ON IN-SERVICE SECONDARY MATHEMATICS TEACHERS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The ability to design technological activities or applets is one of the new challenges for teachers in the context ofdigital learning. Technology teacher training should convert from presenting solutions for teachers, to assist them to becomebetter designers in resolving their own problems. To be able to do that this study used design-based research methodology andworked collaboratively and iteratively, through three iterations with the use of the powerful open-source software GeoGebra.Three theories were used in this study to contribute to our goals: 1) Technological Pedagogical Content Knowledge (TPACK);2) the Diffusion of Innovation Theory; and 3) the Zone Theory. The study is based on a qualitative multiple case study designwith four in-service secondary mathematics teachers (three females and one male) with diverse backgrounds. Analysis of thedata indicated improvements of participants in their utilization of GeoGebra in their practices as well as in their TPACKintegration levels. Unlike the fast improvement in participants’ TPACK, the change in practices was slow, but consideredsustained. In addition, effects of collaboration and iterations with researchers decreased hinderances in GeoGebra integrationand improved some of the assistance factors. With this study we aim to contribute to both theory and practices for teacherprofessional development.